IDENTIFIKASI KUALITAS UDARA DI JALAN JENDRAL AHMAD YANI TANJUNG ENIM KABUPATEN MUARA ENIM - Nurhasana Sinaga; Fera Meliyanti; Berta Afriani (LPPM Universitas Abdurrab, 2025)
Air polluted by fine particles, such as PM2.5 and PM10, significantly affects human health, especially in areas with dense transportation and industrial activities. This study aims to identify air quality on Jalan Jenderal Ahmad Yani, Tanjung Enim, Lawang Kidul District, Muara Enim Regency, in 2024. The method used is a quantitative approach with a cross-sectional design. Measurements were taken at three locations in the morning, afternoon, and evening, using the inScienPro DAZ-400 tool to measure PM2.5, PM10, temperature, humidity, and wind speed. The results showed that the concentrations of PM2.5 and PM10 exceeded the air quality standards, especially at night, with the highest PM2.5 concentration at 12433 µg/m³ and PM10 at 12433 µg/m³. The conclusion of this study is that the air quality in the area is heavily polluted due to heavy vehicle activities, especially coal trucks. It is recommended that the local government consider restricting heavy vehicle traffic during peak hours and regularly monitor air quality to protect public health.